Navigating challenges in hydrocephalus following intraventricular hemorrhage: a comprehensive review of current evidence - Wang, Haozhou; Chen, Xiaofeng; You, Chao; Wu, Ke; Sun, Tong (Frontiers in Neurology, 2025)
Hydrocephalus following intraventricular hemorrhage (IVH) is a complex neurological condition resulting from cerebrospinal fluid (CSF) circulation disruptions due to intraventricular blood entry. This review synthesizes current evidence on pathophysiology, mechanisms, and treatment strategies. Following IVH, erythrocyte lysis releases hemoglobin and iron, triggering oxidative stress and ferroptosis, while thrombin activation, TGF-β1-mediated fibrosis, inflammatory cascades, and ependymal damage collectively contribute to ventricular enlargement. Key animal models elucidate roles of oxidative stress, cytokines, and complement activation in IVH-induced injury. We highlight evolving insights into CSF absorption pathways and blood metabolite interactions, alongside persistent clinical challenges including delayed diagnosis and therapeutic limitations. Experimental approaches such as thrombolytics, iron chelators, and inflammatory inhibitors show preclinical potential but face significant translational barriers: thrombolytics reduced mortality in the CLEAR III trial yet failed to improve functional outcomes or shunt dependence; iron chelation lacks robust clinical validation; and TGF-β1 inhibition yields conflicting efficacy across models. Future research must address the interplay of blood components, inflammatory mediators, and structural damage, prioritizing biomarker discovery and rigorously validated therapeutic innovation.